"Legibility" a product of obligatory processes in parametric architectural design: A study of implications of associative modeling on design thinking in a parametric architectural design studio. (December 2022) - Sardeshpande, Dhanashree; Gokhale, Vasudha
In a problem-based, digital-intensive learning environment, the increased proliferation of computational tools used for architectural design has led to a fundamental transformation in architectural studios. Many studies have shown that this has significantly led to the change in cognition of design environments in academia. Design decisions are made through a recursive process that is cyclically refined by allowing constant feedback and testing. This paper represents an observational study with an aim to understand the impact of digital mediums on design processes and design outcomes focusing on associative modeling using VPL. It contextualizes the difference, the associative modeling system as a parametric subset brings to design thinking when used as a medium to explore architectural design. It analyzes specific attributes of associative modeling, otherwise native to computational thinking, that contribute to the legibility of the design process. The paper demonstrates how associative modeling allows the design process to be examined and edited at any stage during and even after algorithmic development, bringing in flexibility. It is argued that digital design tool affordances enable students to develop multilayered and more structured design logic that augments cognition bringing more legibility to the design thinking process.